Pengaruh Media Augmented Reality dalam Pembelajaran IPAS Terhadap Hasil Belajar Siswa Kelas IV - Riska Mubayyinah Nur Laili; Qurrotu Inayatil Maula (Universitas Palangka Raya, 2024)
The aim of this research is to find out the influence of Augmented Reality use in on the learning outcomes of elementary school students. The research method used is quantitative with a Pre-Experimental design in the form of One-Group Pretest-Posttest. The sampling technique carried out were a non-probability sampling technique, total sampling type. The sample of this research was 34 students of class IV who were treated using Augmented Reality media. This research was carried out at one of the public elementary school in Bangkalan Madura Regency in the 2024/2025 academic year. The data collection techniques used are observation, tests and surveys. Data analysis techniques include prerequisite tests for normality, homogeneity and hypothesis testing. The research results show that there is an influence of the use of Augmented Reality media on the pre-test and post-test results of class IV students. With the results of the hypothesis test analysis, a sig (2-tailed) value <0.05 was obtained with a sig (2-tailed) value of 0.000. It can be concluded that the hypothesis Ha is accepted and Ho is rejected.